POLG determines the risk of sodium valproate induced liver toxicity - Stewart, Joanna D. (2010)
Sodium valproate (VPA) is widely used throughout the world to treat epilepsy, migraine, chronic headache, bipolar disorder, and as adjuvant chemotherapy. VPA toxicity is an uncommon but potentially fatal cause of idiosyncratic liver injury. Rare mutations in POLG, which codes for the mitochondrial DNA polymerase γ (polγ), cause the Alpers-Huttenlocher syndrome (AHS). AHS is a neurometabolic disorder associated with an increased risk of developing fatal VPA-hepatotoxicity. We therefore set out to determine whether common genetic variants in POLG explain why some otherwise healthy individuals develop VPA-hepatotoxicity. We carried out a prospective study of subjects enrolled in the Drug Induced Liver Injury Network (DILIN) from 2004 to 2008 through five US centres. POLG was sequenced and the functional consequences of VPA and novel POLG variants were evaluated in primary human cell lines and the yeast model system Saccharomyces cerevisiae. Heterozygous genetic variation in POLG was strongly associated with VPA-induced liver toxicity (odds ratio = 23.6, 95% CI = 8.4 – 65.8, P = 5.1 × 10(−7)). This was principally due to the p.Q1236H substitution which compromised polγ function in yeast. Therapeutic doses of VPA inhibited human cellular proliferation, and high doses caused non-apoptotic cell death which was not mediated through mitochondrial DNA depletion, mutation, or a defect of fatty acid metabolism. These findings implicate impaired liver regeneration in VPA toxicity, and show that prospective genetic testing of POLG will identify individuals at high risk of this potentially fatal consequence of treatment.